Millennial Tourists in Bali: Motivation, Satisfaction and Revisit Intention - Aridayanti, Dewa Ayu Nyoman; Suryawardani, I Gusti Ayu Oka; Wiranatha, Agung Suryawan (E-Journal of Tourism, 2020)
The Ministry of Tourism of the Republic of Indonesia has developed strategies to attract millennial tourists who are estimated to dominate the world tourism market, where Bali is ranked as the fourth most desirable destination for millennials around the world. One of the important factors for tourists in making a visit decision is motivation. Motivation can affect tourists' satisfaction that is triggered by evaluations through their experiences during a visit and it can affect their revisit intention. Decision making for revisit intention to a destination is actually the behavior of satisfied tourists. This research is a quantitative study with samples of millennial tourists visiting the areas of Ubud, Kuta, Seminyak, Canggu and Uluwatu. Research results were analyzed by Structural Equations Modelling (SEM) analysis usings SmartPLS software 3.0 version. The results showed that motivation consisting of push and pull factors has a significant effect on tourist satisfaction. Tourist satisfaction has a significant effect on the revisit intention. The push factor has a positive but not significant effect on the revisit intention while the pull factor has a significant effect on the revisit intention. Another result showed that 69% of millennial tourists make use of social media as a source of information about Bali. This is also the reason for the facts that 91% of millennial tourists prefer to arrange their own trips. Keyword : Bali, motivation, satisfaction, revisit intention, millennial tourist.